DEVELOPMENT OF PRIVATE HEALTH INSURANCE IN POLAND AND THE PUBLIC HEALTH CARE SYSTEM - Michał KOŚCIÓŁEK; Tomasz TOMCZYK (Modern Management Review, 2020)
In the light of OECD reports and Watch Health Care Foundation research, Poland is on one of the last places in Europe in terms of organization and financing of healthcare services. Due to the inefficiency of the public health care system related to the lack of doctors and the length of waiting for visits to specialists, additional health insurance is a method of improving the health protection standard of Poles. The study presents the condition of the Polish healthcare system and the most important factors influencing the development of private health insurance. As a result of the analysis with use of the zero unitarisation method, it was found that the places where private medical insurance will develop the fastest are Mazowieckie, Śląskie and Dolnośląskie, and it will be more difficult at the so-called eastern wall.